Analisis Produktivitas Alat Hydraulic Static Pile Driver Pada Pembangunan Delft Apartemen Makassar - Dewo Mangiri; Junus Mara; Herby Calvin Pascal Tiyouw (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study aims to find out productivity Hydraulic Static Pile Driver (HSPD) tool in Delft Apartment construction project and also to find out the impact of productivity pilling tool Hydraulic Static Pile Driver on the duration of pilling activities in the Delft Apartement construction project. This study was conducted by direct observation method on project area to get data depth of pilling and duration of work. Then analyzed to get productivity value on Hydraulic Static Pile Driver. The result of this study is the productivity resulting from pilling with Hydraulic Static Pile Driver 15,732 m/hour and the highest productivity value is 21,631 m/hour and the lowest productivity value is 14,933 m/hour. Productivity of Hydraulic Static Pile Driver tool is very impactful to the duration of work pilling. The higher the production value, the shorter the pilling duration, conversely the lower the production value, the longer the pilling duration.